Analisis Bibliometrik Penelitian Kepemimpinan - Purbohastuti, Arum Wahyuni (Journal of Business Management Education (JBME), 2021)
AbstractLeadership is one of the sources of strength in a company, where leadership is a factor in the success of the company. Therefore, leadership is an interesting factor to be investigated further, especially in the 5.0 era where leaders must be able to follow the stability of changes in performance from manual to all-digital. This bibliometric research study aims to determine the number of research articles on leadership, build a map of knowledge to determine the extent of research on leadership, to find out the variables that have been widely studied by researchers related to leadership. This bibliometric research was carried out in stages, namely determining initial keywords in the search method, initial research searches, selecting some literature related to leadership science, analyzing research journals with keywords used using the Publish or perish application and Vosviewer. The result of this research is that the field of leadership is divided into four clusters and 24 items from a span of four years. The first cluster consists of Attention, implications, moderating role, motivation, relations, research, researcher, social learning theory, theory. The second cluster is Importance, knowledge, knowledge sharing, mechanism, mediating role, self, transformational leaders. The third cluster includes Authentic leadership, author, impact, meta analysis. The fourth cluster includes job satisfactions, leadership style, nurse, organizational commitment.Keywords: Bibliometric Analysis and Leadership.